Evaluasi Usability Aplikasi Presensi Mobile UMP Menggunakan Metode User Experience Questionnaire dan Think Aloud - Maulana Ichsan; Feri Wibowo; Harjono Harjono; Abid Yanuar Badharudin (Bulletin of Computer Science Research, 2025)
The implementation of a mobile-based digital attendance system in higher education aims to enhance the efficiency of academic administration and the accuracy of attendance data. However, various challenges remain that impact the quality of user experience, including suboptimal authentication processes, the absence of logout notifications, limited attendance data visualization, and lack of login information storage features. These issues can potentially diminish user convenience and reduce long-term application efficiency. At Universitas Muhammadiyah Purwokerto, a barcode-scanning-based attendance application has been deployed; however, a comprehensive usability and user perception evaluation has not yet been conducted. This study aims to evaluate the usability of the application using a mixed-method approach that combines quantitative and qualitative methods, namely the User Experience Questionnaire (UEQ) and the Think Aloud protocol. The UEQ method is employed to assess user perception across six dimensions: attractiveness, clarity, efficiency, dependability, stimulation, and novelty. In contrast, the Think Aloud method explores users’ real-time verbal feedback and difficulties while interacting with the application. A total of 100 respondents completed the UEQ, and 5 participants took part in the Think Aloud sessions. The results indicate that all UEQ dimensions received positive scores, with clarity scoring the highest (mean = 1.95) and novelty the lowest (mean = 1.35). Findings from the Think Aloud sessions corroborate the UEQ results and reveal previously unidentified areas for improvement. Based on these insights, user-centered design recommendations were developed and translated into a user interface prototype. This study not only provides a comprehensive usability evaluation but also offers direction for the development of a more intuitive and adaptive mobile attendance application that can be adopted by other educational institutions.